2021
DOI: 10.1108/ijph-01-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

From nowhere to nowhere. Homelessness and incarceration: a systematic review and meta-analysis

Abstract: Purpose This study aims to review international literature systematically to estimate the prevalence of homelessness among incarcerated persons at the time of imprisonment and the time of discharge. Design/methodology/approach A systematic review methodology was used to identify quantitative observational studies that looked at the prevalence of homelessness at the time of imprisonment, or up to 30 days prior to that point (initial homelessness), and at the time of discharge from prisons. Studies reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Coupled with attendant systemic and structural inequalities, poverty, homelessness and poor health can (re)produce interactions, involvements and entanglements with the criminal justice system (Couloute, 2018; Halushka, 2020). Previous research showed lower rates of homelessness than what we reported in this study (41.5%) – about 25% among people with incarceration history (Bashir et al , 2021; Kellen et al , 2010; Gulati et al , 2019). This may relate to the use of diagnostic codes to define homelessness and/or that we use a longer observation period of five years for homelessness.…”
Section: Discussioncontrasting
confidence: 71%
“…Coupled with attendant systemic and structural inequalities, poverty, homelessness and poor health can (re)produce interactions, involvements and entanglements with the criminal justice system (Couloute, 2018; Halushka, 2020). Previous research showed lower rates of homelessness than what we reported in this study (41.5%) – about 25% among people with incarceration history (Bashir et al , 2021; Kellen et al , 2010; Gulati et al , 2019). This may relate to the use of diagnostic codes to define homelessness and/or that we use a longer observation period of five years for homelessness.…”
Section: Discussioncontrasting
confidence: 71%
“…Criminal justice contact is common amongst homeless people. Estimates vary from about half to two‐thirds of the homeless population having been incarcerated at some stage according to studies in high income countries (Roy, Crocker et al., 2014; Saddichha, Fliers et al., 2014), while in a systematic review and meta‐analysis of 17 studies of incarcerated persons, the pooled prevalence estimate was that 23% had been homeless prior to incarceration (Bashir, Moloney et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The isolation, confinement, and danger of the prison environment can have damaging long-term psychological consequences (Sykes, 2007). Further, after reentry, formerly incarcerated individuals often face job loss, homelessness (Bashir et al, 2021), and discrimination (Assari et al, 2018), all of which have been associated with depression. Further, several studies have found that depression is associated with increased risk of FI (Garg et al, 2015; Hanson & Olsen, 2012).…”
Section: Introductionmentioning
confidence: 99%